Blood Pressure and Risk of Cognitive Impairment: The Role of Vascular Disease in Neurodegeneration - Mar Carmona-Abellan; Malwina Trzeciak; Miriam Recio Fernández; Beatriz Echeveste; Laura Imaz; Maria-Rosario Luquin; Mario Riverol (Brain Sciences, 2021)
(1) Background: Both cerebral vascular disorders and cognitive decline increase in incidence with age. The role of cerebral vascular disease and hemodynamic changes in the development of cognitive deficits is controversial. The objective of this study was to assess the cardiovascular response during cardiac stress testing in neurologically asymptomatic individuals who developed cognitive impairment several years after previous cardiac stress testing. (2) Methods: This was a retrospective cohort study of patients who underwent cardiac stress testing between January 2001 and December 2010. Patients were followed up until May 2015, and we selected those who developed cognitive dysfunction including dementia, mild cognitive impairment, and subjective cognitive decline, after the stress test. Heart rate and blood pressure both at rest and at peak exercise, and the mean R-R interval at rest were recorded. For each patient who developed cognitive impairment, we selected one matched control who did not show cognitive decline by the end of the follow-up period. (3) Results: From the cohort of 7224 patients, 371 developed cognitive impairment; of these, 186 (124 men) met the inclusion criteria, and 186 of the other patients were selected as matched controls. During follow-up, cognitive impairment appeared 6.2 ± 4.7 years after the cardiac stress test. These patients who had subsequently developed cognitive impairment had significantly lower at-rest systolic, diastolic, and mean blood pressure than controls (p < 0.05). Further, compared with controls, their maximum heart rate was significantly higher at peak exercise. (4) Conclusion: The results from this study suggest that differences in cardiovascular response to stress might be present in individuals who develop cognitive decline. These findings challenge the possibility of assessing blood pressure and heart rate variability at rest and during cardiac stress as potential risk factors associated with cognitive impairment.